Validation of Analytical Method for Determining Formaldehyde Levels in Imported Apples Sold in Pontianak City using UV–Vis Spectrophotometry - Gaudensius Rizky; Fajar Nugraha; Hadi Kurniawan (Journal of Food and Pharmaceutical Sciences, 2026)
The Indonesian government has implemented various efforts to protect food from biological, chemical, and physical contaminants that may endanger public health. Formaldehyde, an aqueous solution containing 37% formaldehyde, is commonly used as an antiseptic, disinfectant, and preservative for biological specimens. However, its misuse in food products, such as imported apples, remains a concern in Indonesia. This study aims to detect and measure formaldehyde levels in imported apples sold in Pontianak City by comparing peeled and unpeeled samples. Qualitative analysis was conducted using Schiff reagent color tests, while quantitative analysis employed UV-Vis spectrophotometry. The results showed the presence of formaldehyde in unpeeled imported apples, with concentrations ranging from 5.23–22.65 mg/kg (1.57–6.80 mg/serving). Meanwhile, peeled imported apples exhibited lower formaldehyde levels, ranging from 2.55–6.75 mg/kg (0.76–2.02 mg/serving) across six districts in Pontianak City. Statistical testing with the Independent Sample T-Test showed a significant distinction between peeled and unpeeled imported apples. Therefore, peeling imported apples prior to consumption may reduce potential exposure to formaldehyde. Consumers are advised to wash apples thoroughly under running water and purchase products from reliable sources to minimize the risk of contamination. Furthermore, strengthened regulatory monitoring and stricter enforcement against the illegal use of formaldehyde in food products are necessary to ensure consumer safety and protect public health.